Supply- and demand-side factors affecting maize and cowpea varietal turnover and quality seed use: Mixed-method evidence from northern Nigeria - Ragasa, Catherine; Umar, Sulaiman; Sani, Rabiu Mohammed; Onyibe, Johnson E.; Omoigui, Lucky; Fasoranti, Adetunji; Nwagboso, Chibuzo; Bamiwuye, Temilolu; Takeshima, Hiroyuki; Andam, Kwaw S. (International Food Policy Research Institute, 2024)
This study provides an integrated assessment of the seed system for maize and cowpea, two of the most important crops in Nigeria. We analyze the various factors influencing seed supply and demand and present different measures of capacity and incentive of multiple actors along the seed value chain. We also present metrics on adoption of improved varieties and quality seed use, given the complexity of these concepts and persistent challenges in measuring them in a survey context. At the national level, the 2015 to 2018 Living Standards Measurement Survey data show that the adoption rate of improved varieties was 16 percent of maize area and 6 percent of cowpea area, with 9 percent of maize farmers and 3 percent of cowpea farmers reporting certified seed use of improved varieties. Data from household surveys conducted in 2022 show that in Bauchi and Kaduna—states with relatively high maize and cowpea production levels—the adoption rate of quality seeds of improved varieties was 10 percent of cowpea land area and 25 percent of maize land area. In addition, the improved varieties in the cowpea and maize plots were old; the area-weighted varietal age in cowpea farms was 12 years and in maize farms, 13 years. The most popular cowpea variety was Kananado (likely matching released variety SAMPEA 9 or SAMPEA 11, released in 2005 and 2009, respectively), and the most popular maize variety was SAMMAZ 15, released in 2008. Newer varieties have not caught up in popularity.